Accelerated outgrowth in cross‐facial nerve grafts wrapped with adipose‐derived stem cell sheets. (9th July 2020) - Fujii, Kaori; Matsumine, Hajime; Osaki, Hironobu; Ueta, Yoshifumi; Kamei, Wataru; Niimi, Yosuke; Hashimoto, Kazuki; Miyata, Mariko; Sakurai, Hiroyuki
Abstract: In this study, we devised a novel cross‐facial nerve grafting (CFNG) procedure using an autologous nerve graft wrapped in an adipose‐derived stem cell (ADSC) sheet that was formed on a temperature‐responsive dish and examined its therapeutic effect in a rat model of facial palsy. The rat model of facial paralysis was prepared by ligating and transecting the main trunk of the left facial nerve. The sciatic nerve was used for CFNG, connecting the marginal mandibular branch of the left facial nerve and the marginal mandibular branch of the right facial nerve. CFNG alone, CFNG coated with an ADSC suspension, and CFNG wrapped in an ADSC sheet were transplanted in eight rats each, designated the CFNG, suspension, and sheet group, respectively. Nerve regeneration was compared histologically and physiologically. The time to reinnervation, assessed by a facial palsy scoring system, was significantly shorter in the sheet group than in the other two groups. Evoked compound electromyography showed a significantly higher amplitude in the sheet group (4.2 ± 1.3 mV) than in the suspension (1.7 ± 1.2 mV) or CFNG group (1.6 ± 0.8 mV; p < .01). Toluidine blue staining showed that the number of myelinated fibers was significantly higher in the sheet group (2, 450 ± 687) than in the suspension (1, 645 ± 659) or CFNG group (1, 049 ± 307; p < .05). CFNG in combination with ADSC sheets, prepared using temperature‐responsive dishes, promoted axonal outgrowth in autologous nerve grafts and reduced the time to reinnervation.